Parcelas de comprobacion y participacion del agricultor - Maître, Adrian; Molina, JP (International Center for Tropical Agriculture, 1989)
This working document presents a proposal to integrate the verification of promising technology with farmer participation in the research process. A case study, already half finished, is presented in which the proposed methodology has been applied. (AS- CIAT)